Readaptação funcional de docentes na rede estadual paulista: a necessidade de uma compreensão complexa - Oliveira, Rosemary Gonçalves de (2021)
The situations experienced in the readaptation process by basic education teachers in the public school system of the state of São Paulo affect their subjectivities, expressed in the ways of being and being in the world, to the point of resisting the condition of being readapted, even knowing that they can perform other activities inherent to the field of school education. In this sense, the actions that are part of public policies developed in this functional readaptation process constitute the object of this research. It aims to understand how they affect teachers in the readaptation process and, specifically, 1) identify which actions the state education network develops in the process of functional readaptation of its teachers; 2) know the experiences and expectations of teachers who are readapted; 3) analyze and relate the actions developed with the experiences of the research participants. The hypothesis is that these actions do not meet the specificities of the teachers in functional readaptation because they are isolated, fragmented and do not consider the subject/teacher. The qualitative research methodological approach employs the techniques of interview and documental survey. The imaginary complexes, complex understanding, cultural imprinting and ecology of action are the principles of complex thinking in Edgar Morin, which constitute the theoretical framework. Obtained as results: the actions during the functional readaptation process are linked to the guarantee of the right and far from educational public policies aimed specifically at this professional public; the responsible departments have mismatched and non-systematized information; Resolution SE 74 of 2017 is the only normative related to public policy for this segment, but it is not implemented; the bureaucratic fragmentation adopted by the managerialist model management, the delay in conducting the process, the vision of the medical expertise, the authoritarian postures of managers, the deficiencies of medical and health care constitute a matrix mark in the educational culture, an imprinting, of prejudice and stigma about readapted teachers; the interviewees perform a movement of resistance and make the ecology of action when finding themselves in the new function. The study points out that it is possible for the state to propose and implement actions that meet the specificities of this group of professionals based on a complex understanding that considers the objective and subjective conditions of being a readapted teacher in the São Paulo state education system.